MÁS ALLÁ DE LOS “DATOS”: UNA BREVE REFLEXIÓN DESDE LA EPIDEMIOLOGÍA SOCIAL A LOS SISTEMAS TRADICIONALES DE INFORMACIÓN Y VIGILANCIA DE LA VIOLENCIA - Castillo Vargas, Andrés (Universidad de Costa Rica, 2019)
The main purpose of this article is to present some theoretical reflections on the characteristics, functions and importance of social epidemiology in traditional systems of information and surveillance of violence. With this objective, violence is addressed as a public health problem, which transcends numerical factors and converges with sociocultural and historical variables, incorporating theoretical and methodological aspects of social epidemiology. The results of this reflection allow us to contemplate both the relevance and the need for the agencies in charge of designing and putting into practice the information systems, to know in depth the proposals of social epidemiology. As a conclusion, this work proposes that the social problems of public health be  considered from the integral and collective perspective of the human processes posed by social epidemiology.